2020
DOI: 10.26480/trab.02.2020.52.56
|View full text |Cite
|
Sign up to set email alerts
|

Response of Sulphur and Zinc Nutrition to the Seed Yield and Oil Content of Mustard (Cv. Bari Sarisha-14)

Abstract: The role of different nutrient elements is well established in plant metabolism. However, different crops respond differently in relation to their growth and yield. An experiment was conducted at the Agronomy Field Laboratory, Bangladesh Agricultural University, Mymensingh to evaluate the response of sulphur and zinc nutrition to the seed yield and oil content of mustard (cv. BARI Sarisha-14). It, laid out in RCBD with three replications was consisted of four levels of sulphur (0, 20, 40 and 60 kg ha-1) and Zn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
0
0
0
Order By: Relevance
“…It makes some contributions to protein synthesis by orchestrating the folding and structural stability of a protein [6]. Some research showed the positive effect of sulfur on the yield of oil seed crops, such as groundnut [7], rapeseed [8], mustard [9], sesame [10], sunflower [11], and soybean [12,13]. Several field studies have demonstrated that the application of sulfur in conjunction with nitrogen in soybean fields has resulted in a significant increase in seed yield.…”
Section: Introductionmentioning
confidence: 99%
“…It makes some contributions to protein synthesis by orchestrating the folding and structural stability of a protein [6]. Some research showed the positive effect of sulfur on the yield of oil seed crops, such as groundnut [7], rapeseed [8], mustard [9], sesame [10], sunflower [11], and soybean [12,13]. Several field studies have demonstrated that the application of sulfur in conjunction with nitrogen in soybean fields has resulted in a significant increase in seed yield.…”
Section: Introductionmentioning
confidence: 99%
“…Zn has been found to have a stimulating effect on pod development, seed formation, and oil synthesis in mustard seeds (Halim et al, 2023). Additionally, it has been observed to enhance the overall yield of mustard in terms of both seed and stover production (Sinha et al, 2000;Sultana et al, 2020). The significance of zinc fertilisers in augmenting mustard yield is widely acknowledged, albeit with limited research conducted in Bangladesh regarding the impact of these fertilisers on mustard crops.…”
Section: Introductionmentioning
confidence: 99%